Crystal Properties and Interaction with Hydroxamic Acid Collectors of Bastnaesite Insights from First-Principles Calculations - Wang, Weiwei (Langmuir : the ACS journal of surfaces and colloids, 2025)
This study systematically investigates the crystal properties of bastnaesite and the adsorption mechanisms of salicylhydroxamic acid (SHA) and 2-hydroxy-3-naphthyl hydroxamic acid (2-H-3-NHA) onto the bastnaesite (100) surface using density functional theory (DFT) calculations. Computational results indicate that bastnaesite cleavage primarily occurs along Ce-O and Ce-F ionic bonds during dissociation, with the {100} plane identified as the most preferential cleavage direction due to its lowest surface energy. The chemical reactivity and adsorption behaviors of both collectors were thoroughly examined with adsorption energy calculations quantifying their surface affinity. Comparative analysis reveals that 2-H-3-NHA demonstrates significantly greater adsorption stability and chemical reactivity than SHA. This enhanced performance is attributed to the naphthalene ring's superior steric hindrance effect and the presence of longer carbon chains compared to the benzene ring in SHA. These findings are consistent with results from the pure mineral flotation tests. Collectively, this work provides an atomic-level understanding of hydroxamic acid collector interactions with bastnaesite surfaces, offering valuable guidance for designing high-performance rare earth mineral flotation reagents